Buttons-on-demand using shape memory alloys - Alif Danial Mohamed Jumari (Nanyang Technological University, 2022)
Buttons-on-demand are buttons that will serve as a human interaction platform in cars or in electronic readers (e-readers) for the blind. These buttons can be realised by using an electrical circuit when required and will remain protruded for activation. When they are no longer needed, they will be retraced to a flat position and become inactive.